HYPOLIPIDEMIC ACTIVITY OF ETHANOLIC EXTRACTS OF CASSIA ANGUSTIFOLIA IN TRITON- X 100 INDUCED HYPERLIPIDEMIA IN RATS - Nanumala, Shravan Kumar; Nischal, Y.; Sarika, M.; Sri Sai Shravya, G. (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Aim- The present study was aimed to evaluate Hypolipidemic activity of ethanolic extracts of Cassia angustifolia in Triton X 100 induced Hyperlipidemia in Rats. Materials and Methods- Anti-hyperlipidemic activity was evaluated using Triton 100-induced hyperlipedemia in rats as an experimental model. Plasma triglycerides, Total cholesterol, HDL, LDL, VLDL were determined to assess the hypolipidemic activity. Result- It was found that the EECA and 400 mg/kg dose showed significant hypolipidemic effect (P<0.01) where as 300 mg/kg also significant in the entire parameter used for evaluation of hypolipidemic effect (P<0.05). Conclusion- Ethanolic extracts of cassia angustifolia showed that hypolipidemic effect and this study provide scientific proof for their tradinitional claims. However further study is needed in order to understand the precise mechanism. Key words Cassia angustifolia, Hypolipidemia, Atorvastatins.